2002
DOI: 10.1088/0953-8984/14/20/312
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and magnetic properties of LaTMg and CeTMg (T = Pd, Pt, Au)

Abstract: The title compounds were prepared from the elements by reactions in sealed tantalum tubes in a water-cooled sample chamber of a high-frequency furnace. They crystallize with the ZrNiAl-type structure, space group P6̄2m. The structures of the cerium compounds were refined from single-crystal x-ray diffraction data: a = 767.3(1) pm, c = 410.37(4) pm, wR2 = 0.0324, 521 F2-values for CePdMg; a = 755.02(7) pm, c = 413.82(4) pm, wR2 = 0.0393, 514 F2-values for CePtMg; and a = 774.1(3) pm, c = 421.6(1) pm, wR2 = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…In contrast to the investigation by Gibson et al [33], no magnetic ordering has been reported for CePdMg. Ce 2 Ni 2 Mg, and CeNi 4 Mg are intermediate-valent compounds.…”
Section: Article In Presscontrasting
confidence: 83%
See 2 more Smart Citations
“…In contrast to the investigation by Gibson et al [33], no magnetic ordering has been reported for CePdMg. Ce 2 Ni 2 Mg, and CeNi 4 Mg are intermediate-valent compounds.…”
Section: Article In Presscontrasting
confidence: 83%
“…The lanthanum and cerium based series LaTMg and CeTMg (T ¼ Pd, Pt, Au) [33] have been investigated in detail. All three lanthanum compounds show Pauli paramagnetism down to 0.3 K. Cerium is in a stable trivalent oxidation state in the CeTMg (T ¼ Pd, Pt, Au) compounds.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the platinumbased series we were recently able to further reduce the VEC by substitution of indium by magnesium. In ZrNiAl-type CePtMg [7], magnesium takes part in the covalently bonded [PtMg] network and the magnetic ordering temperature is 3.6 K. Several systems like CeAuIn 1−x Mg x show complete solid solubility [8]. We have now started a more systematic investigation of the corresponding zinc-based systems, in order to elucidate similarities to the magnesium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our systematic phase analytical studies of ternary RE x T y Mg z compounds we have now focused on the platinum-based systems. So far only the equiatomic compounds REPtMg (RE ¼ La, Ce, Pr, Nd, Sm, Gd) [16][17][18], and the rare earth-rich compounds RE 4 PtMg (RE ¼ Y, Nd, Sm, Gd) [19] have been synthesized. Herein we report on the new series RE 23 Pt 7 Mg 4 (RE ¼ La, Ce, Pr, Nd, Sm) with Pr 23 Ir 7 Mg 4 type structure.…”
Section: Introductionmentioning
confidence: 99%